2022
DOI: 10.3390/e24121754
|View full text |Cite
|
Sign up to set email alerts
|

A New X-ray Medical-Image-Enhancement Method Based on Multiscale Shannon–Cosine Wavelet

Abstract: Because of noise interference, improper exposure, and the over thickness of human tissues, the detailed information of DR (digital radiography) images can be masked, including unclear edges and reduced contrast. An image-enhancement algorithm based on wavelet multiscale decomposition is proposed to address the shortcomings of existing single-scale image-enhancement algorithms. The proposed algorithm is based on Shannon–Cosine wavelets by taking advantage of the interpolation, smoothness, tight support, and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The proposed method effectively enhances the texture, increasing the brightness and contrast, suppress the noise and obtained MSE= 4.85E+3, PSNR= 25.96, Entropy= 7.88. Liu et al [11] proposed an algorithm which is based on Shannon-cosine wavelets; a multi-scale interpolation wavelet operator is constructed to divide the image into sub-images from high frequency to low frequency. And perform different multi-scale wavelet transform on the detailed image of each channel.…”
Section: Cmentioning
confidence: 99%
“…The proposed method effectively enhances the texture, increasing the brightness and contrast, suppress the noise and obtained MSE= 4.85E+3, PSNR= 25.96, Entropy= 7.88. Liu et al [11] proposed an algorithm which is based on Shannon-cosine wavelets; a multi-scale interpolation wavelet operator is constructed to divide the image into sub-images from high frequency to low frequency. And perform different multi-scale wavelet transform on the detailed image of each channel.…”
Section: Cmentioning
confidence: 99%
“…Traditional image enhancement algorithms have certain effects in both natural image and medical DR image enhancement (especially in natural image enhancement), such as histogram equalization (HE) [6], adaptive histogram equalization (AHE) [7], contrast-limited adaptive histgram equalization (CLAHE) [8]- [10], nonlinear enhancement based on wavelet decomposition [11]- [14], enhancement based on Gauss-Laplacian pyramid [15]- [17] and other algorithms. These traditional enhancement algorithms have some inherent problems.…”
Section: Introductionmentioning
confidence: 99%
“…The final results showed that the recommended technique was effective in increasing the contrast of X‐ray images. Liu et al 23 proposed a Shannon‐Cosine wavelet‐based method. Following the division of the image into several sub‐images from high frequency to low frequency using a multiscale interpolation wavelet operator, the detailed image of each channel is subjected to various multiscale wavelet transforms.…”
Section: Introductionmentioning
confidence: 99%